1991
DOI: 10.1177/000992289103001004
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial Fibroelastosis With Coronary Artery Thromboembolus and Myocardial Infarction

Abstract: We report a case of an 18-month-old male, born to a woman with third trimester febrile illness, who had a history of congestive heart failure and respiratory distress, cardiomegaly, and electrocardiographic (ECG) findings suggestive of cardiomyopathy and myocarditis. After gradual improvement in heart size and function with pharmacologic therapy, he developed a terminal episode of respiratory distress and cardiogenic shock, with ECG findings of an anterolateral infarct. At autopsy it was found that endocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It is one of the causes of heart failure in infants and children [6,7]. Patients with EFE are prone to endocardial thrombosis, which may be due to enlarged cardiac cavity, systolic dysfunction, and altered endothelium lining [8,9]. Previous studies have also reported that a thrombus can easily form at the sites of akinetic, dyskinetic, or aneurysmal segments that are potentially at risk for thromboembolism [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the causes of heart failure in infants and children [6,7]. Patients with EFE are prone to endocardial thrombosis, which may be due to enlarged cardiac cavity, systolic dysfunction, and altered endothelium lining [8,9]. Previous studies have also reported that a thrombus can easily form at the sites of akinetic, dyskinetic, or aneurysmal segments that are potentially at risk for thromboembolism [10].…”
Section: Discussionmentioning
confidence: 99%
“…A total of seven patients diagnosed with EFE with thrombosis were identi ed. A summary of these patients is presented in Table 1 [8,9,[11][12][13]. There were one female and six males, with the age at diagnosis ranging from fetal to 68 years old.…”
Section: Discussionmentioning
confidence: 99%
“…stenosis and hypoplastic left heart syndrome [28]; nonetheless, the exact aetiology is unknown. The underlying pathophysiology of endocardial fibroelastosis is the deposition of acellular fibrocartilaginous tissue in the subendothelial layer of the endocardium predominantly involving the inflow tracts and apices of ventricles [29], and intraventricular thrombi formation are an additional complication that CMR can detect [30].…”
Section: What Are the Aetiologies That Mainly Affect The Paediatric P...mentioning
confidence: 99%
“…Deposition of acellular fibrous and cartilaginous tissue in the subendothelial layer of the endocardium, more frequently involving the inflow tracts and apices of both ventricles leads to severe left ventricular diastolic impairment with restrictive cardiomyopathy, with a possible evolution towards dilated cardiomyopathy ( 87 , 88 ). Other features are papillary muscles shortening with severe mitral regurgitation and mural thrombus formation ( 89 , 90 ). CMR is also a valuable tool for diagnosing EFE in children born from anti-SSA/SSB antibodies positive mothers.…”
Section: Cardiovascular Involvement In Sjogren’s Syndromementioning
confidence: 99%